The Effect of Endorser Credibility on Purchasing Decisions of NEO Coffee Products (Study of the 2019 Palembang NCTzen Community Members Who Consumed NEO Coffee Products) - Andina, R.A.; Meilinda, Nurly (HM Publisher, 2019)
The purpose of this study is to determine whether there is an influence of endorser credibility on purchasing decisions of NEO Coffee products and how much influence is given. The theory used to measure the effect of endorser credibility (independent variable) is the TEARS Model Theory proposed by Shimp (2014) and for purchasing decisions of NEO Coffee products (dependent variable) using Kotler and Keller's (2009) theory. The method applied is a quantitative method with descriptive analysis techniques and explanatory techniques that use simple linear regression parametric statistical analysis tools. Data collection was carried out through the distribution of questionnaires to 70 respondents of the 2019 Palembang NCTzen Community Consumers who consumed NEO Coffee Products with a purposive sampling technique. The findings from the analysis of the data in this study were obtained through hypothesis testing using the ???? test that itungcount greater than abeltable where itungcount 8.404> abeltable 1.994, which means that there is an influence of endorser credibility on purchasing decisions of NEO Coffee products, and the effect exerted at 50.9 % and the rest are influenced by other factors. The linear regression equation obtained is ????̂ = 8.269 + 0.879 ???? which means that each addition of one endorser credibility value will give an increase of 0.879 to the decision of purchasing NEO Coffee products among 2019 NCTzen Palembang community members who consume NEO Coffee products.